(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The researcher identified the carefully studied phenomena (social competence, psychological competence, and adequacy of planning in sports training), and a scale for each variable was built on a sample of (70) players. The scientific method for each of the indicators of validity and reliability. The study aimed to: • Construct a scale for the studied variables. • Finding the relationship between the adequacy of planning in sports training with the social and psychological competence of the coaches of Premier League clubs from the players’ point of view. The standards for coaches of Premier League clubs were applied to the application sample of (120) players to reach conclusions, the most important of which are: A - The ability of the measures of the studied variables to cover their variables. B - There is a significant correlation between the adequacy of planning in sports training, social competence and psychological efficiency. T - The level of the actual performance of the trainers for the variables studied was medium.